FINANCIAL LEVERAGE IN EUROPEAN AND AMERICAN FINANCIAL THEORY: HISTORICAL EVOLUTION AND STRATEGIC ROLE IN MODERN ORGANIZATIONS - Abduqodirova Mohinur Anvar qizi (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Abstract. This study explores the idea of financial leverage within the European and American financial traditions, through examining historical evolution, practical implications in organizational finance. As the concept of leverage means utilizing borrowed money, despite both traditions perceiving financial leverage as using borrowed capital in order to amplify return on equity. According to their different structure, tax, and risk factors, as well as their interpretations, also vary. The dual nature of leverage is explored in this article, its potential to improve profitability, and its inherent financial risks via emphasizing its strategic role in decision-making. In this paper, comparative methodology is employed, with fundamental ideas, and this study attempts to gather contemporary applications. As it is obvious from the concept of leverage, it is a powerful instrument that can enhance the value of an investment when used properly, but when it is misused can pose severe financial instability. Since the main aim of the research is to provide policymakers and corporate managers with an integrated perspective and a useful roadmap for decision making.